2018
DOI: 10.1245/s10434-018-6565-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Outcomes of Pathologic T1-2N1 Breast Cancer After Mastectomy: Looking Beyond Locoregional Failure Rates

Abstract: Patients with pT1-2pN1 represent a heterogeneous group with a wide range of LRF/DM rates. In particular, patients with pT1 tumors and 1 + LN, and patients with micrometastases, had low event rates. These groups would derive small absolute reductions in LRF and DM with addition of PMRT, underscoring the importance of patient selection for PMRT in pT1-2pN1 breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
3
22
2
Order By: Relevance
“…This new pathological substaging seems promising, but very few studies have validated these new substages of stage T1-2N1 disease [ 19 ]. There is also some controversy about the effect of chemotherapy and postmastectomy radiotherapy (PMRT) in patients with stage T1-2N1 disease [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. To the best of our knowledge, no studies so far have tried to determine the effect of locoregional and systemic treatment in this patient subset.…”
Section: Introductionmentioning
confidence: 99%
“…This new pathological substaging seems promising, but very few studies have validated these new substages of stage T1-2N1 disease [ 19 ]. There is also some controversy about the effect of chemotherapy and postmastectomy radiotherapy (PMRT) in patients with stage T1-2N1 disease [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. To the best of our knowledge, no studies so far have tried to determine the effect of locoregional and systemic treatment in this patient subset.…”
Section: Introductionmentioning
confidence: 99%
“…As a heterogenous disease, T1-2N1 breast cancer harbors a broad range of risks for disease progression [ 12 ] and calls for more tailored treatment, especially in the era of precision medicine guided by molecular subtypes [ 3 ]. Thus, we performed this retrospective analysis of T1-2N1 breast cancer patients according to subtypes trying to identify those patients who would benefit from PMRT.…”
Section: Introductionmentioning
confidence: 99%
“…The present study indicated that radiotherapy played an important role in improving the survival outcomes for patients with T1-2N1 breast cancer, and clinicians should be cautious to omit radiotherapy after mastectomy in this group, although increasing data showed low-risk of locoregional recurrences in T1-2N1 breast cancer treated with modern systemic therapy [22][23][24]. We found that the BCS + RT group had comparable survival outcomes with the MRM + RT group, but the radiation volume in the two groups was not the same.…”
Section: Discussionmentioning
confidence: 73%